2023
DOI: 10.1101/2023.08.08.552539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac function and ECM morphology are altered with high fat diets inDrosophila

Abstract: Cardiovascular disease is characterized by aberrant and excessive extracellular matrix (ECM) remodelling, termed fibrosis. Fibrotic remodelling is typically triggered by inflammation, which occurs systemically in obesity. Despite the contribution of fibrosis to adverse clinical outcomes and disease progression, there are no available treatments for this condition. Developing therapeutics for chronic conditions requires an understanding ofin vivoECM regulation, and how the ECM responds to a systemic challenge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Characterization of this overgrowth phenotype revealed that giant larvae grow to immense sizes without exhibiting hallmarks of obesity, including low triglyceride levels, reduced lipid droplet size, and gene expression reflecting an increase in mobilization of stored lipids, as well as decreased lipogenesis (Beller et al 2010; Hehlert et al 2019). This is in contrast to previous studies that have demonstrated obesity symptoms in response to high fat diet treatments (Birse et al 2010; Guida et al 2019; Andrews et al 2023). This indicates that giant larvae attain their size by overgrowth, not fat storage.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Characterization of this overgrowth phenotype revealed that giant larvae grow to immense sizes without exhibiting hallmarks of obesity, including low triglyceride levels, reduced lipid droplet size, and gene expression reflecting an increase in mobilization of stored lipids, as well as decreased lipogenesis (Beller et al 2010; Hehlert et al 2019). This is in contrast to previous studies that have demonstrated obesity symptoms in response to high fat diet treatments (Birse et al 2010; Guida et al 2019; Andrews et al 2023). This indicates that giant larvae attain their size by overgrowth, not fat storage.…”
Section: Discussioncontrasting
confidence: 99%
“…Triglyceride (TG) levels however were significantly lower in both male and female giant larvae ( Figure 1C) . Elevated TG levels have previously been noted in response to high fat diet (HFD) treatments that result in obesity phenotypes (Birse et al 2010; Guida et al 2019; Andrews et al 2023). We investigated further by labelling lipid droplets ( Figure 1D ) within the fat body and quantifying their diameter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations